Kinetic and structural insights into the grain boundary phase transitions in Ni-Bi alloys. (15th February 2023) - Bian, B.; Taheriniya, S.; Muralikrishna, G. Mohan; Godha, A.; Makineni, S.K.; Sankaran, S.; Straumal, B.B.; Du, Y.; Wilde, G.; Divinski, S.V.
Abstract: Kinetic and structural changes associated with grain boundary phase transition induced by Bi alloying in dilute Ni–Bi alloys (0–0.3 at.% of Bi) are investigated in a concerted manner. Grain boundary diffusion of Ni in the Ni-Bi alloys is measured in Harrison's B- and C-type kinetic regimes applying the radiotracer technique and utilizing the 63 Ni radioisotope. The measurements are performed across the single phase towards two-phase regions of the bulk phase diagram. In case of the single phase region it is the Ni(Bi) solid solution. In case of two phase areas these are Ni(Bi) solid solution + liquid Bi above 927 K or Ni(Bi) solid solution + NiBi below 927 K. Three distinct regions of the dependence of the Ni grain boundary diffusion rates on the Bi concentration are distinguished. A slight increment in Ni grain boundary diffusion is observed at lower Bi contents which is driven by Bi grain boundary segregation. Beyond a critical Bi concentration and still within the single-phase solid solution region, the Ni diffusivity starts to enhance dramatically with increasing Bi content. This is correlated with the appearance of multi-layer Bi segregation along the grain boundaries. It is substantiated by high-angle annular dark-field scanning transmission electron microscopy combined with energy dispersive X-ray spectroscopy measurements. At higher Bi concentrations, which corresponds to the appearance of a liquid layer of Bi at the grain boundaries, the Ni diffusivity attains the highest values. A serial of structural transitions between the different grain boundary phases is for the first time demonstrated to be accompanied by remarkable changes of the grain boundary diffusion rates. The present results highlight a close correlation between the atomic transport and structure modifications due to grain boundary phase transitions in the Ni–Bi alloys. Utilizing the present experimental results, a Ni–Bi grain boundary diffusion map is proposed. Graphical abstract: Image, graphical abstract